A new process for the evaluation of the net-benefit of flexible ground-floor ceiling in the face of use transition uncertainty. (January 2018) - Martani, Claudio; Cattarinussi, Laurent; Adey, Bryan T.
Abstract: In metropolitan areas, real estate investments, such as buildings, can be highly profitable. The profitability, however, can be uncertain, as adaptations might be required in the long-term to enable the modification of the building to adapt it to new uses. In building adaptation for use transitions, an important aspect is the modification of the ceiling height of the ground floor to meet the floor height requirements of different uses. Designs that include flexible ceilings instead of rigid ceilings have relatively low future adaptation costs, but are relatively expensive. Such designs are, therefore, only beneficial when the use transition costs over the life of the building are higher than the cost difference between the flexible and the rigid design. Because of the difficulties in predicting the number and types of adaptations that will occur over the life of a building, and the fact that flexible designs are more expensive, investors, to their own detriment, often build rigidly for current needs only. In the work presented in this article, a new process was developed and tested that uses Monte Carlo simulations to estimate costs and benefits of alternative ceiling designs, considering uncertainty on use transitions. The process is shown by using it to estimate the net-benefit over 70 years for an investor related to a fictive building in London with flexible ceilings and the same building with rigid ceilings. It was considered that multiple use transitions among five use categories (residential, retail, industrial, office, and other) were possible. It is shown that the process can be used to gain more insight into how buildings should be designed to maximize investor net-benefit, taking into consideration uncertain variables, such as use-change rate, construction costs and durations, discount factors and rents. A discussion of possible improvements to the process is given. Highlights: Design choices based on average conditions don't guaranty optimal investments. Ceiling design optimization requires considering the uncertainty on use transitions. A Monte-Carlo based process is proposed to design ceilings considering uncertainty. In dense urban areas the process is needed to optimize ceiling investments.